2018
DOI: 10.1055/s-0036-1591941
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Synthesis of Substituted Pyrazoles from One-Pot Reaction of Ketones, Aldehydes, and Hydrazine Monohydrochloride

Abstract: An efficient, one-pot and metal-free process for the preparation of 3,5-disubstituted and 3,4,5-trisubstituted pyrazoles on multi-gram scale was developed. One-pot condensation of ketones, aldehydes and hydrazine monohydrochloride readily formed pyrazoline intermediates under mild conditions. Oxidation of pyrazolines, in situ, employing bromine afforded a wide variety of pyrazoles. The methodology offers a fast, and often chromatography-free protocol for the synthesis of 3,4,5-substituted pyrazoles in good to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 3 publications
(2 reference statements)
0
11
0
1
Order By: Relevance
“…Finally, aerial oxidation of pyrazoline intermediate 7 provided the desired 4-alkyl-substituted pyrazole 3m (Scheme ). The observation of the reduction of yield of a reaction, which was carried out under an argon atmosphere (Table , entry 13), further supported the aerial oxidation of pyrazoline intermediate 7 . The observation of a mass value of 353.1972 in the high-resolution mass spectrometry (HRMS) indicates the presence of one, more, or all intermediates 4 – 7 in the reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, aerial oxidation of pyrazoline intermediate 7 provided the desired 4-alkyl-substituted pyrazole 3m (Scheme ). The observation of the reduction of yield of a reaction, which was carried out under an argon atmosphere (Table , entry 13), further supported the aerial oxidation of pyrazoline intermediate 7 . The observation of a mass value of 353.1972 in the high-resolution mass spectrometry (HRMS) indicates the presence of one, more, or all intermediates 4 – 7 in the reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
“…157 Lellec, Chen, and Yang demonstrated that a three-component cyclization between trifluoroacetone (394), benzaldehyde, and hydrazine gave pyrazoline 395 (Scheme 66). 158 Oxidation of the latter with oxygen in dimethyl sulfoxide under heating gave pyrazole 97 in 66% yield. In 2018, Fox and collaborators from Bristol-Myers Squibb developed a practical strategy to obtain 3bromo-and 3-chloropyrazoles.…”
Section: Other Fluorinated Enaminonesmentioning
confidence: 99%
“…Substituted pyrazolines can be synthesized in one-pot procedures. For example, condensation of carbonyl compounds and hydrazine hydrochloride in methanol for 1 h at 65 • C produced substituted pyrazolines [27]. They can also be produced from 3-butynol and arylhydrazines through hydrohydrazination in the presence of a catalyst containing zinc [28].…”
Section: Introductionmentioning
confidence: 99%